Bacteriologic Profile and Antibiogram of the Blood Culture Isolates in Febrile Children - Pant, Shyam Prasad; Chandi, Dhruba Hari; Karki, Rajan (International Journal of Innovative Research in Medical Science, 2017)
Bacteraemia is a common condition in children with a resultant high morbidity and mortality. There are limited data on the etiology and characteristics of bloodstream infections in children. Objectives: The aim of this study was to determine the bacteriological profile and antibiotic sensitivity pattern of blood culture isolates. Methods: Blood cultures from 2831 febrile children below 15 years of age presenting to Kanti Children Hospital, Kathmandu; Nepal from June 2011 to April 2012 were examined. The growths from subcultures were identified by conventional biochemical tests and serological tests. Antibiotic susceptibility testing to antibiotics was performed by Kirby Bauer disc diffusion method. Results: The positivity of blood culture was 5% (142/2831). Gram positive and gram negative bacteria constituted 59.1% and 40.9% respectively. The most prevalent bacterial isolates were Staphylococcus aureus (52.1%) and Escherichia coli (23.2%). The study showed that the most effective drugs against S. aureus were Aamikacin and Chloramphenicol and against E. coli were Amikacin, Chloramphenicol and Ciprofloxacin. The most sensitive and preferable among the tested antibiotics was Chloramphenicol and Cephalosporins were most ineffective drugs. Conclusion: This study highlights the variable nature of antibiotic susceptibility patterns and stresses the need for continuous screening and surveillance of antibiotic resistance in pediatric care unit.